The Effect of Movement Control Order on Quality of Life among Staffs in Faculty of Sport Science and Recreation UiTM Shah Alam - Ismail, Mohammad Alif; Nazeri, Ahmad Fadhil; Zailan, Nur Ain Iwani; Ilias, Noor Fatihah (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
Coronavirus known as COVID-19 is a respiratory illness that affects people worldwide. Malaysia was also affected by this virus; therefore, the government announced the Movement Control Order (MCO) to break the COVID-19 chain. MCO possibly affects quality of life of working people. Therefore, the purpose of this study is to compare the effect of MCO on quality of life between academic and administrative staff in Faculty of Sport Science and Recreation, UiTM Shah Alam. This study utilised causal – comparative research design involved academic and administrative staff. The sample analysed were N=52 comprised of 30 academic and 22 administrative staff. This study used SF-36 questionnaire to measure quality of life. Data was collected via online. T-test was used to identify the differences between the two groups. Academic staff quality of score was (M=56.90 ± 6.97) and administrative staff was (M=59.7 ± 7.54) score. The findings reported that there is no significant difference in quality of life, p = 0.669 between academic and administrative staff during MCO. Quality of life for both academic and administrative staff was affected during MCO due to COVID-19 pandemic.